Reading in the experience biographies in Arabic and Malay poetry - Mohammed, Nafea hammad; Gawad, Siham Hasan (Opción, 2019)
The research aims to comparing the poetic biography in Arabic poetry and Malay poetry to the importance of this literary genre. Research follows the method of analytical approach in the analysis of self-dimensions and reading their approaches in the poetic text in a flexible coordinate tool. As a result, the Arab poet Ibrahim Nasrallah and the Malaysian poet Abdul Aziz Darman poets always resort to the retrieval of the past and experience. In conclusion, the spirit of writing in this framework reveals to us a social, intellectual and human mind enjoyed by the Arab and Malay personality.